Biomarkers for risk-based treatment modifications for CNS germ cell tumors: Updates on biological underpinnings, clinical trials, and future directions - Takami, Hirokazu; Ichimura, Koichi (Frontiers in Oncology, 2022)
CNS germ cell tumors (GCTs) preferentially occur in pediatric and adolescent patients. GCTs are located predominantly in the neurohypophysis and the pineal gland. Histopathologically, GCTs are broadly classified into germinomas and non-germinomatous GCTs (NGGCTs). In general, germinoma responds well to chemotherapy and radiation therapy, with a 10-year overall survival (OS) rate of approximately 90%. In contrast, NGGCTs have a less favorable prognosis, with a five-year OS of approximately 70%. Germinomas are typically treated with platinum-based chemotherapy and whole-ventricular radiation therapy, while mature teratomas can be surgically cured. Other NGGCTs require intensive chemotherapy with radiation therapy. Long-term treatment-related sequelae, including secondary neoplasms and cerebrovascular events, have been well recognized. These late effects have a tremendous impact in later life, especially since patients are mostly affected in childhood or early adulthood. With the aim of minimizing the treatment burden on patients, identification of biomarkers for treatment stratification as well as evaluation of treatment response is of critical importance. Recently, tumor cell content in germinomas has been shown to be closely related to prognosis, suggesting that cases with low tumor cell content may be safely treated with a less intensified regimen. Among the copy number alterations, the 12p gain is the most prominent and has been shown to be a negative prognostic factor in NGGCTs. MicroRNA clusters (mir-371-373) were also revealed to be a hallmark of GCTs, demonstrating the potential for the application of liquid biopsy in the diagnosis and detection of recurrence. Recurrent mutations have been detected in the MAPK or PI3K pathways, most typically in KIT and MTOR and that low genome-wide methylation has been demonstrated in germinoma; this most likely reflects the cell-of-origin primordial germ cells for this tumor type. These alterations can also be leveraged for liquid biopsies of cell-free DNA and may potentially be targeted for treatment in the future. Advancements in basic research will be translated into clinical practice and can directly impact patient management. Additional understanding of the biology and pathogenesis of GCTs will lead to the development of better-stratified clinical trials, ultimately resulting in improved treatment outcomes and a reduction in long-term treatment-related adverse effects.